Characterization of Resistive Hotspots induced in Superconducting NbTi thin film by an electrical current pulse. (26th May 2021) - Harrabi, K; Mekki, A; Bahlouli, H; Mathieu, P
Abstract: We report on the creation of resistive states in NbTi superconducting filament on polished crystalline Al2 O3 using the current driven pulse technique. A current pulse larger than the depairing current (Ic ) initiates a dissipation in a localized spot. The non-equilibrium state described by the two dissipative mechanism pinpointed as hotspot and phase slip center. A time dependent voltage response exposes the collapse of superconductivity that occurs after a certain delay time td . We found that hotspots occur at temperatures much lower than the transition temperature. This can be clearly seen in a current versus temperature diagram. The thermal cooling and heat escape times were extracted from fitting the experimental data of the delay time to Tinkham's amended version of the Time-Dependent Ginzburg-Landau (TDGL). The temperatures reached at the core of hotspots were determined without any parameter adjustment.